Analysis of climate extreme indices - Adeyeri, Oluwafemi E.; Lawin, Agnidé Emmanuel; Laux, P.; Ishola, K.A; Ige, S.O (Elsevier, 2019)
This study investigates trends of climate extreme indices in the Komadugu-Yobe Basin (KYB) based on observed data of the period 1971–2017 as well as regional climate model (RCM) simulations for the historical period (1979–2005), the near future (2020–2050), and the far future (2060–2090). In order to correct change points in the time historical series, the Adapted Caussinus Mestre Algorithm for homogenising Networks of Temperature series homogeneity test is used. The magnitude of the linear trends is estimated using the Sen's slope estimator and Mann-Kendall's test is performed to check the statistical significance of the trends. Future trends are assessed using the ensemble mean of eight regional climate model data under two emission scenarios, provided by the Coordinated Regional Climate Downscaling Experiment (CORDEX). Therefore, the projected rainfall and temperature have been corrected for biases by using empirical Quantile Mapping. In the observations, warm spell duration, warm day-, and warm night frequencies exhibit statistically significant positive trends. Although there is a positive trend in the annual total rainfall, the number of consecutive wet (dry) days decreases (increases). The future climate also shows a continuing positive trend in the temperature extreme indices as well as more frequent extreme rainfall events. Therefore, it is pertinent for decision-makers to develop suitable adaptation and mitigating measures to combat climate change in the Basin.
In recent decades, there has been an increase in the frequency, intensity and extent of the impact of natural disasters on the environment which is a concern to many nations. This has been attributed to climate change and environmental degradation (Lyon and DeWitt, 2012). Ly et al. (2013) argued that climate variability is mainly associated with increasing concentration of anthropogenic greenhouse gases in the atmosphere. This has resulted in global warming. Over the Sudanian, Sahelian and Sahelo-Saharan ecological zones of West Africa, there has been an increasing trend of both maximum and minimum temperatures with minimum temperatures increasing more rapidly (Ly et al., 2013).
Keywords: Homogeneity; Climate extreme indices; Linear trends; Bias correction; Komadugu-Yobe basin; Lake Chad region